The Long Pentraxin PTX3 as a Link Between Innate Immunity, Tissue Remodeling, and Cancer - Doni, Andrea; Stravalaci, Matteo; Inforzato, Antonio; Magrini, Elena; Mantovani, Alberto; Garlanda, Cecilia; Bottazzi, Barbara (Frontiers in Immunology, 2019)
The innate immune system comprises a cellular and a humoral arm. Humoral pattern recognition molecules include complement components, collectins, ficolins, and pentraxins. These molecules are involved in innate immune responses by recognizing microbial moieties and damaged tissues, activating complement, exerting opsonic activity and facilitating phagocytosis, and regulating inflammation. The long pentraxin PTX3 is a prototypic humoral pattern recognition molecule that, in addition to providing defence against infectious agents, plays several functions in tissue repair and regulation of cancer-related inflammation. Characterization of the PTX3 molecular structure and biochemical properties, and insights into its interactome and multiple roles in tissue damage and remodelling support the view that microbial and matrix recognition are evolutionarily conserved functions of humoral innate immunity molecules.